Analisis Tingkat Kesulitan Belajar Matematika Siswa dalam Menggunakan Prinsip Matematis - Pramesti, Cicik; Prasetya, Ariesandi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
In the world of education there are still many students who have difficulty learning mathematics. Difficulty learning mathematics is a condition, a person is not able to learn mathematics well. The difficulty in learning mathematics is related in mentioning things that are known and asked for, calculating (counting), and application of formulas. Based on these circumstances, the researcher conducted a study that aims to analyze the difficulties of learning mathematics in using the principles of determinant and inverse matrix material. This learning difficulty was analyzed based on indicators of learning difficulties in mathematics using the principles of (1) calculation errors or algebraic operations, (2) unable to determine relevant data, and (3) unable to apply formulas. This type of research is descriptive qualitative, with the research instruments are tests and interviews. The descriptions of the results of the analysis of the difficulty of learning mathematics in using the principles are: (1) the calculation error indicator is still at a high level criterion, so that the students' numeracy skills still need to be improved, especially in terms of accuracy, accuracy, and caution; (2) the inability to determine relevant data is at the medium level criteria, but this ability can still be improved again by getting used to writing things that are known and asked for to make it easier to solve mathematical problems; and (3) the indicators of not being able to apply the formula are at low level criteria, which are dominated by low-ability students. This difficulty can be minimized by direct mentoring by the teacher and or through peer tutors.